PEMANFAATAN LINGKUNGAN SOSIAL SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Mukhamad Murdiono (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Civic education is the subject that is very tight his connection with socialproblems. The problem that developed in the community when beingbrought to the classroom as the material instruction for the student,however difficult to be solved because abstract. Therefore the use of themedia really is needed in civic education learning. The teacher can use thesocial environment as the media in civic education learning. Using thesocial environment as the media instruction will make the teaching andlearning process more significant because the students are faced with thereal fact and condition naturally. There are some advantages that wereobtained from the activity studied the social environment in the teachingdan learning process, sttch as: the activity studied mort:? interesting anddid not bore, learned to be more significant, materials that were studiedmore rich and factual, the learning activity more comprehensive andactive, the studying source became richer, and the student moreunderstood and experienced aspects of the available life fully inenvironment.